The Role of Specific Eye Care Exercise Combined with 0-20-20 Vision Rule in Managing Computer Vision Syndrome among Computer Users. - J., Afreen fathima; Suganthirababu, Prathap; Kumaresan A.; Srinivasan, Vignesh; Vishnuram, Surya; Dhanusiya; Priyadharshini K. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Digital Eye Strain (DES) has enhanced one of the crucial well-being matters with the expanded utilization of digitalized gadgets with optical revealing. Common digital eye strain manifestations include eye strain, headaches, blurred vision, and neck or shoulder pain, which typically get worse the more video display terminals (VDT)users use them. Very little investigation has been done to show how digital use affects Indian users' physical health, particularly among college undergraduate. Purpose: To find the effect of specific eye care exercise combined with 20-20-20 vision rule in managing computer vision syndrome among computer users. Methods: Seventy-four participants were selected for inclusion and exclusion criteria. They were divided into two groups: 20-20-20 Vision Rule Group (37) and conventional group (37). The pre and post-test values will be measured by computer vision syndrome - questionnaire. Group-A received 20-20-20-vision rule along with eye exercise and group-B received specific eye exercise. Both programs were given for 2 weeks, weekly 6 days. Results: Using Computer vision syndrome-questionnaire, 20-20-20 vision rule group's post-test mean was 25.51 and whereas conventional group's was 29.35. This demonstrates that the conventional group received a higher score of digital eye strain symptom positive than the 20-20-20 vision rule group. Conclusion: Specific eye care exercise combined with 20-20-20 vision rule in managing Digital Eye Strain among digital users was found to be more successful than specific eye exercise in reducing manifestation of Digital Eye Strain.